The Multiproduct Monopolist Under Vertical Differentiation: an Inductive Approach - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
The behaviour of a multiproduct profit seeking monopolist is evaluated vis à vis that of a social planner, in a model where there is a continuum of consumers characterized by different marginal willingness to pay for quality. When the market is completely covered, the monopolist undersupplies all qualities as long as their number is finite. When quality becomes continuous, the richest consumer is provided with the socially optimal quality. Under the alternative assumption of partial market coverage, the monopolist supplies the same qualities as the social planner, restricting though total output. Finally, it turns out that, for a given number of varieties, under partial market coverage the monopolist can make at least as good as under full market coverage, so that she prefers to distort quantity rather than quality.
Keywords: 330